1976
DOI: 10.1039/c39760000699
|View full text |Cite
|
Sign up to set email alerts
|

π–π Aggregation in metalloporphyrins: causative factors

Abstract: The strength of aggregation in PdII, Nin, ZnII, and CdII metalloporphyrins is shown by n.m.r. spectroscopy to depend upon interaction of the metal ion with the porphyrin .rr-system; within a selected series of 2,4-disubstituted deuteroporphyrin-IX dimethyl esters complexed with a constant metal ion the aggregation is further enhanced by the presence of electron-withdrawing substituents on the porphyrin periphery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…The reactions were carried out by refluxing an ethanolic solution of the 3,4-disubstituted pyrrole with an excess of formaldehyde and a strong acid such as hydrobromic acid. 15 The resulting macrocycles were then air oxidised to the corresponding porphyrins over a period of a week. Slow oxidation gives better yields than procedures involving bubbling air through the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reactions were carried out by refluxing an ethanolic solution of the 3,4-disubstituted pyrrole with an excess of formaldehyde and a strong acid such as hydrobromic acid. 15 The resulting macrocycles were then air oxidised to the corresponding porphyrins over a period of a week. Slow oxidation gives better yields than procedures involving bubbling air through the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Essentially all of the observed peaks from the solid S phase can be indexed as (hk) reflections arising from a 2-D square lattice, with a lattice parameter a increasing from 20.6 Å for the C 8 compound, to 24.5 Å for the 10 C 12 derivative, with only a wide-angle peak at approximately 4.5 Å being associated with the periodicity of the stacking along the columns. From these data we are strictly speaking unable to determine whether the columns are completely untilted with respect to the x-y plane of the square lattice 15 (tetragonal symmetry) or slightly tilted (monoclinic symmetry). In the latter case reflections such as (100) and (010) etc.…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was attributed to π-π aggregation which is a well known phenomenon for metalloporphyrins. 27 1 H NMR studies on metalloporphyrins reported in the literature demonstrated that the strength of aggregation is dependent on the interaction of the metal ion with the porphyrin π-system. The aggregation was enhanced by the presence of electron-withdrawing substituents on the porphyrin periphery.…”
Section: Synthesismentioning
confidence: 99%